From Security to Ethics: Evolution of Indonesia’s Ideology in Media Discourse - Yuzril Fadhil Muhammad; Farida Farida; Nevrettia Christantyawati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study analyzes the dynamics of Indonesian digital ideology in the national online media discourse throughout 2024–2025, focusing on issues such as the National Data Center (PDN), public data leaks, ransomware attacks, and the repositioning of digital ethics by the state through the Ministry of Communication and Digital Affairs (Komdigi). The approach used is Critical Discourse Analysis (CDA), combining the models of Norman Fairclough, Teun A. van Dijk, and Ruth Wodak, to examine the relationship between text structure, discourse practice, and ideological social practice. Data was obtained from seventeen online news articles from Tempo.co, analyzed based on the structure of the title, lead, and body. The results show that Indonesian digital discourse has undergone an ideological shift from the hegemony of techno-nationalism to public moral resistance, ending in the restoration of digital ethics. State discourse focuses on “security” and “data sovereignty” to legitimize power, while the media and the public construct counter-narratives based on ‘transparency’ and “privacy.” These findings confirm that digital language has become a new political arena where the legitimacy of power and public resistance are negotiated through media discourse. The results of this study are expected to contribute to the development of digital ethics governance and political communication literacy in Indonesia.